Acculturative stress level among international postgraduate students of a public university in Malaysia - Ye, H. D.; Juni, Muhamad Hanafiah (Community Health Society Malaysia, 2017)
Background: Acculturative stress among international students is a serious issue, resulting of linguistic and cultural differences in the host country. Levels of acculturative stress vary among different groups of international students who may encounter different problems. While international postgraduate students tend to take more stress from academic concerns, financial burdens as well as responsibility for family. Therefore, the aim of this study is to determine the acculturative stress level of international postgraduate students in Malaysia. Materials and Methods: A cross-sectional study was conducted among the international postgraduate students in a public university in Malaysia, using multistage random sampling proportionate to the size from six faculties in the university. Data was collected using a pretested, self-administered questionnaire consisting of socio-demographic factors and Perceived Stress Scale (PSS) with 10 items. Data was analysed using IBM SPSS version 22.0. Descriptive analysis was used to determine the factors contributed to acculturative stress. Ρ value of less than 0.05 was considered statistically significant. Result: A total of 404 respondents were assessed in this study, with the response rate of 82.1%. The obtained data showed that the prevalence of moderate acculturative stress was 77.7%, with 5.2% high stress. Mean age of the respondents was 32 years, whereas the majority of respondents (75.7%) were male students. Respondents were mainly from Middle East (42.3%) and Africa (37.1%). There were 71.5% international students living without their spouses/ single/ alone and 28.5% accompanied by their family while studying at UPM. Conclusion: The findings of the study reveal that over four fifths of international postgraduate students studied were in moderate to high acculturative stress level. Female students, Christian religion group, and those who came from Middle East had more possibilities to experience higher levels of stress compared to other groups of international students.